SYNTACTIC STYLISTIC DEVICES (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
This article explains stylistic syntactic devices as a general syntactic type of language, analyzes syntactic stylistic procedures, and provides instances of them. The standard also covers how a given language is used in various historical stages of its history, taking into account phonetic, morphological, syntactic, and stylistic principles of speech. Inversion, indivisible structures, parallel devices, repetition, ellipse, gradation, and other topics are covered in the article.